Higher Cho/NAA Ratio in Postoperative Peritumoral Edema Zone Is Associated With Earlier Recurrence of Glioblastoma - Cui, Yong; Zeng, Wei; Jiang, Haihui; Ren, Xiaohui; Lin, Song; Fan, Yanzhu; Liu, Yapeng; Zhao, Jizong (Frontiers in Neurology, 2020)
Objective: To explore the prognostic significance of metabolic parameters in postoperative peritumoral edema zone (PEZ) of patients with glioblastoma (GBM) based on proton magnetic resonance spectroscopy (MRS). Methods: The postoperative MRS data of 67 patients with GBM from Beijing Tiantan Hospital were retrospectively reviewed. Metabolite ratios including Cho/NAA, Cho/Cr and NAA/Cr in both postoperative PEZ and contralateral normal brain region were recorded. Log-rank analysis and Cox regression model were used to identify parameters correlated with progression-free survival (PFS) and overall survival (OS). Results: Compared with the contralateral normal brain region, postoperative PEZ showed a lower ratio of NAA/Cr (1.20±0.42 vs. 1.81±0.48, P<0.001), and higher ratios of Cho/Cr and Cho/NAA (1.36±0.44 vs. 1.02±0.27, P<0.001 and 1.32±0.59 vs. 0.57±0.14, P<0.001). Both the ratios of Cho/NAA and NAA/Cr were identified as prognostic factors in univariate analysis (P<0.05), while only Cho/NAA≥1.31 was further confirmed as an independent risk factor for early recurrence in the Cox regression model (P<0.01). According to the factors of MGMT promotor unmethylation, without radiotherapy and Cho/NAA≥1.31, a prognostic scoring scale for GBM was established, which could divide patients into low-risk, moderate-risk, and high-risk groups. There was a significant difference of survival rate between the three groups (P<0.001). Conclusions: Higher Cho/NAA ratio in the postoperative PEZ of GBM predicts earlier recurrence and is associated with poor prognosis. The prognostic scoring scale based on clinical, molecular and metabolic parameters of patients with GBM can help doctors to make more precise prediction of survival time and to adjust therapeutic regimens.